The Effectiveness of Using Physics Module with Problem-Based Learning to Enhance Critical and Creative Thinking Skills - suharno, Suharno; Selviana, Afifah Shafa; Sunarno, Widha (Journal of Education Reseach and Evaluation, 2022)
Module is one of the teaching materials that really helps students in learning process. However, the modules used in schools are still lacking in emerging 21st-century’s skills, especially in critical and creative thinking skills. Thus, the researcher conducted this research to analyze the effectiveness of using module as a teaching material to improve critical and creative thinking skills of high school students. The method used is quantitative research with normality and homogeneity prerequisite tests and the N-gain test to check the effectiveness of using module in Physic learning process. The data used is the students’ learning result. The researcher uses Shapiro-Wilk normality test which shows the significance value of pretest is 0.153 and posttest is 0.052. Based on the homogeneity test using Levene's Test, the significance is 0.615 and indicating homogeneous data. The average N-gain value for all aspects of critical thinking skills is 0.68, so the improvement is in moderate category. Meanwhile, the average N-gain value for all aspects of creative thinking skills is 0.47 and the betterment is also in moderate category. According to the results, it can be concluded that Physics Module with problem-based learning has been effectively used in Physics learning to improve critical and creative thinking skills of high school students in moderate category.